International evidence-based consensus diagnostic and treatment guidelines for unicentric Castleman disease - van Rhee, Frits (Blood Adv, 2020)
Castleman disease (CD) includes a group of rare and heterogeneous disorders with characteristic lymph node histopathological abnormalities. CD can occur in a single lymph node station, which is referred to as unicentric CD (UCD). CD can also involve multicentric lymphadenopathy and inflammatory symptoms (multicentric CD [MCD]). MCD includes human herpesvirus-8 (HHV-8)–associated MCD, POEMS-associated MCD, and HHV-8(−)/idiopathic MCD (iMCD). The first-ever diagnostic and treatment guidelines were recently developed for iMCD by an international expert consortium convened by the Castleman Disease Collaborative Network (CDCN). The focus of this report is to establish similar guidelines for the management of UCD. To this purpose, an international working group of 42 experts from 10 countries was convened to establish consensus recommendations based on review of treatment in published cases of UCD, the CDCN ACCELERATE registry, and expert opinion. Complete surgical resection is often curative and is therefore the preferred first-line therapy, if possible. The management of unresectable UCD is more challenging. Existing evidence supports that asymptomatic unresectable UCD may be observed. The anti–interleukin-6 monoclonal antibody siltuximab should be considered for unresectable UCD patients with an inflammatory syndrome. Unresectable UCD that is symptomatic as a result of compression of vital neighboring structures may be rendered amenable to resection by medical therapy (eg, rituximab, steroids), radiotherapy, or embolization. Further research is needed in UCD patients with persisting constitutional symptoms despite complete excision and normal laboratory markers. We hope that these guidelines will improve outcomes in UCD and help treating physicians decide the best therapeutic approach for their patients.